The role of the nurse practitioner and childhood Obesity - Buckley, Joan; Bennett-Murray, Judith (Cultura del cuidado, 2018)
To remove barriers that prevent nurses from leading, changing and advancing health care, the Robert Wood Johnson Foundation (RWJF), and the Institute of Medicine (IOM) launched an initiative in 2008 that would transform the nursing profession. In 2010, the appointed RWJF Committee on the Future of Nursing, made the recommendation at the IOM, that nurses practice to the full extent of their education and training; not for the purpose of saving money, but to be a part of the transformation of a seamless, quality healthcare delivery system that improves health outcomes (The future of nursing: the Institute of Medicine (IOM) issues report, 2010; Russell-Babin, Wurmser, 2016). The Centers for Disease Control (CDC) (2011 - 2014) reported that in the United States, more than one-third of adults and 17% of children between the ages of two and nineteen are obese (Ogden, Carroll, Kit, & Flegal, 2014). These epidemic numbers are of great concern worldwide when the long-term effects of diabetes, cardiovascular disease, hypertension, and cancer will have the potential to overwhelm healthcare systems (Bergman, Stefanovski, Buchanan, Sumner, Reynolds, Sebring, Xiang, & Watanabe, 2011). The Nurse Practitioner will transform healthcare and the effects of co-morbidities, such as obesity on the nation’s population (RussellBabin, Wurmser, 2016).